(782) The Impact of Licences loans and Foreign Trade of Industrialization تأثير قروض التراخيص والتجارة الخارجية على التصنيع - Knauthe, Erhart (INP, 2024)
The purpose of this paper is to answer some basic questions which are just under discussion in the UAR, The process of industrialization is not like a weekend trip because serious constraints have to be solved in order to construct a homogeneous industrial society. In the UAR the industrial society no doubt will have an important agricultural back-ground. But industrialization will completely change the face of the country. From this point of view it must be ensured that the new industries contribute to the increase of national income in such an extent that the demands can be satisfied on increasingly higher level, despite of the growth of population./